2018 IEEE Biomedical Circuits and Systems Conference (BioCAS) 2018
DOI: 10.1109/biocas.2018.8584808
|View full text |Cite
|
Sign up to set email alerts
|

ECG Arrhythmia Classification Using Transfer Learning from 2- Dimensional Deep CNN Features

Abstract: Due to the recent advances in the area of deep learning, it has been demonstrated that a deep neural network, trained on a huge amount of data, can recognize cardiac arrhythmias better than cardiologists. Moreover, traditionally feature extraction was considered an integral part of ECG pattern recognition; however, recent findings have shown that deep neural networks can carry out the task of feature extraction directly from the data itself. In order to use deep neural networks for their accuracy and feature e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
69
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(70 citation statements)
references
References 6 publications
0
69
0
1
Order By: Relevance
“…We also used 1-D ECG signals as input to the CNN model used in experiments and achieved a classification accuracy of 97.80%. In recent years, 2-D CNN models have also been used, by converting the 1-D ECG signals to 2-D representation, with noticeable performance [16]. Towards this end, the proposed model was based on a 2-D representation of the ECG data to efficiently apply 2-D CNN models and benefit from the flexibility of data augmentation in such methods.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We also used 1-D ECG signals as input to the CNN model used in experiments and achieved a classification accuracy of 97.80%. In recent years, 2-D CNN models have also been used, by converting the 1-D ECG signals to 2-D representation, with noticeable performance [16]. Towards this end, the proposed model was based on a 2-D representation of the ECG data to efficiently apply 2-D CNN models and benefit from the flexibility of data augmentation in such methods.…”
Section: Resultsmentioning
confidence: 99%
“…The techniques presented in literature have been applied to smaller datasets; however, for the purpose of generalization, the performance should be tested on larger datasets. There are methods reported that use 2-D ECG signals [16,45]; however, to the best of our knowledge, there are not clear details on how the 1-D ECG signal is converted to 2-D images for using 2-D CNN models. Most methods have been tested on only a few types of arrhythmia and must be evaluated on all major types of arrhythmia.…”
Section: Our Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of deep learning-based approaches have also been adopted recently for arrhythmia classification [14]- [26]. In [14]- [19], 1D convolutional neural network (CNN) and in [23]- [25], recurrent neural network (RNN) and LSTM network are employed while in [20]- [22], 2D CNN is used by converting 1D ECG beats into 2D images. Most of the deep learning-based approaches are facing some common issues: (1) raw ECG data collected from patients are being directly fed to the deep neural network making the classification process complicated due to presence of various low and high-frequency noises, (2) for dealing with 1D ECG signal, data augmentation is not necessarily used and even if it is used, natural variational pattern of ECG isn't properly captured or preserved, and (3) most of the approaches use very deep CNNs with large number of parameters that not only increase the computational complexity but also lead to overfitting the model to training data.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the methods mentioned thus far, some scholars have used short-term Fourier and wavelet transforms to convert ECG data into two-dimensional (frequency, time) data and used them as input for a deep neural network. Salem et al [14] used the transformation "spectrogram" from a one-dimensional (1D) ECG signal from the MIT-BIH dataset and the European ST-T dataset to make 2D images. They also used a 161-layer DenseNet, pre-trained on millions of images, to extract abstract information and then applied an SVM for four-class classi cation (Normal Sinus/Atrial Fibrillation and Flutter/Ventricular Fibrillation/ST Segment Change).…”
Section: Introductionmentioning
confidence: 99%